Strongly connected dominating set construction algorithm balancing time delay and energy consumption - Yan-jing SUN; Jian-sheng QIAN; Shan-shan MA; Peng REN (Tongxin xuebao)
To the asymmetry of link in wireless sensor networks,a problem about the strongly connected dominating tree with bounded transmission delay (SDTT) was put forward.The distributed strongly connected dominating tree (SCDT) algorithm was also proposed to construct strongly connected dominating set balancing transmission delay and energy consumption.Firstly,it constructed a maximal independent set (MIS) based on a unit disk graph,and then implemented the SCDT algorithm based on a double weighted and directed graph fulfilling the requirements of energy consumption and transmission delays simultaneously.The theoretical analysis and simulation results show that the presented algorithm can correctly solve the SDTT problem and construct the connected dominating sets(CDS)with constraints to form virtual backbone.